Fibrin‐targeted plasminogen activation by plasminogen activator, PadA, from Streptococcus dysgalactiae. (5th April 2014) - Singh, Satish; Bhando, Timsy; Dikshit, Kanak L.
Abstract: Bacterial plasminogen activators differ from each other in their mechanism of plasminogen activation besides their host specificity. Three‐domain streptokinase (SK) and two‐domain PauA generate nonproteolytic active site center in their cognate partner plasminogen but their binary activator complexes are resistant to α2‐antiplasmin (a2AP) inhibition causing nonspecific plasminogen activation in plasma. In contrast, single‐domain plasminogen activator, staphylokinase (SAK), requires proteolytic cleavage of human plasminogen into plasmin for the active site generation, and this activator complex is inhibited by a2AP. The single‐domain plasminogen activator, PadA, from Streptococcus dysgalatiae, having close sequence and possible structure homology with SAK, was recently reported to activate bovine Pg in a nonproteolytic manner similar to SK. We report hereby that the binary activator complex of PadA with bovine plasminogen is inhibited by a2AP and PadA is recycled from this complex to catalyze the activation of plasminogen in the clot environment, where it is completely protected from a2AP inhibition. Catalytic efficiency of the activator complex formed by PadA and bovine plasminogen is amplified several folds in the presence of cyanogen bromide digested fibrinogen but not by intact fibrinogen indicating that PadA may be highly efficient at the fibrin surface. The present study, thus, demonstrates that PadA is a unique single‐domain plasminogen activator that activates bovine plasminogen in a fibrin‐targeted manner like SAK. The sequence optimization by PadA for acquiring the characteristics of both SK and SAK may be exploited for the development of efficient and fibrin‐specific plasminogen activators for thrombolytic therapy.